DESAIN DAN OPTIMISASI STAND ALONE PV PANEL SYSTEM UNTUK BUDIDAYA UDANG VANNAMEI PADA KOLAM BUNDAR DI KABUPATEN LOMBOK UTARA - Birham Hermansyah; Aryani Rahmawati; Barokah Barokah (Politeknik Kelautan dan Perikanan Bitung, 2022)
Cultivating vannamei shrimp using round ponds is an alternative way of cultivation to minimize the significant investment costs. One of the obstacles in vannamei shrimp cultivation is the availability of Dissolve Oxygen (DO) in water. By utilizing solar energy which is converted into electrical energy, DO levels can be maintained with an aeration system that utilizes solar energy. North Lombok Regency has the potential for solar energy which reaches 4.91 kWh / m2 / day with a minimum clearness index of 0.446 which is very potential to be utilized. The purpose of this research is to find the optimal design for a stand alone panel PV system to serve the electrical energy needs of vannamei shrimp farming in round ponds. The method used is to calculate the most optimal design with HOMER (Hybrid Optimization Model for Electric Renewables) software to be able to serve the average energy requirement of 38.2 kWh / day. From the analysis, it was found that the most optimal designs were the PV panel brand A 16.8 kW, the PV panel brand B 1 kW and the 200 Ah battery with a total of 104 units. Keywords : cultivation, energy, optimization, pv panel, shrimp